Lagrangian Observation of 234Th and Its Application in Constraining the Sinking of Particulate Organic Carbon on the Slope of the Northeastern South China Sea - Yang, Weifeng; Zhao, Xiufeng; Chen, Min; Qiu, Yusheng; Zheng, Minfang (Frontiers in Marine Science, 2022)
The 234Th–238U disequilibrium has been widely used to quantify the sinking flux of particulate organic carbon (POC) out of the upper ocean. However, the influence of the advection on the quantification is poorly understood due to the lack of in situ measured physical parameters. Here, a Lagrangian observation was deployed for 39 h to track the variability of 234Th along with the current on the slope of the northeastern South China Sea (SCS). Contrasting to the general ocean interior, 234Th showed deficits relative to 238U in the mesopelagic waters, indicating an enhanced removal of 234Th. Concurrently, elevated total particulate matter (TPM) and POC contents were observed in the mesopelagic waters, supporting the driving force of the cross-shelf dispersion of re-suspended shelf/slope sediments for the 234Th removal. The widely used 234Th-model (ignoring physical processes) produced a much lower sinking flux of POC than the sediment trap-derived POC flux during the same observation, indicating an unneglectable influence of advection and diffusion. By considering the main horizontal advection and vertical diffusion, the 234Th–238U method gave rise to comparable results to sediment trap. 234Th-derived POC fluxes showed an increased pattern from 300 to 1,000 m, consistent with the more abundant POC where. These results indicated that advection represents an unneglectable process during the quantification of the sinking flux of 234Th over the slope of the SCS.